APHORPINE ALKALOIDS FROM BARK OF Cryptocarya ferrea - Nurdin Saidi; A. Hamid A. Hadi; Khalijah Awang; Mat Ropi Mukhtar (Indonesian Journal of Chemistry, 2009)
Isolation, identification and characterization of the compounds isolated from the bark of Cryptocarya ferrea yielded three known aphorpine alkaloids. They are (-)-O-methylisopiline 1, (+)-norlirioferine 2 and (+)-lirioferine 3. Structural elucidation was established through several spectroscopic methods, such as 1D-NMR (1H, 13C, DEPT, NOE), 2D-NMR (COSY, NOESY, HMQC, HMBC), UV, IR, and MS and comparison with the published data.